Современная наука и проблема универсалий - Лещенко, Н. Р. (ХНУРЕ, 2019)
The importance of science in modem world is hard to overestimate. The benefits of scientific progress are used in everyday life of the billions of people nowadays. Still, problems of a different kind occur. Those problems disturb not only the minds of the scientists, but also the minds of the philosophers. This work is mostly devoted to the development of the discussion between thinkers of the 20th century around the problem of universals and its connection with philosophy of science. Also, the work presents a short introduction to the philosophy of D.C. Williams and his view on the problem of universals.